A case of non‐alcoholic steatohepatitis complicated with severe acute pancreatitis induced by decreased lipoprotein lipase and hepatic triglyceride lipase activity levels in a young Japanese woman. Issue 9 (18th July 2018) - Minohara, Sawa; Bae, Sung Kwan; Sugiyama, Saori; Shibata, Noriko; Gushima, Toshifumi; Motoshita, Junichi; Shimoda, Shinji; Takagi, Atsuko; Ikeda, Yasuyuki; Takahashi, Kazuhiro
Key Clinical Message: We report a case of non‐alcoholic steatohepatitis complicated with acute pancreatitis induced by hypertriglyceridemia in a young Japanese woman. A precise examination of the lipid profile showed decreased lipoprotein lipase (LPL) and hepatic triglyceride lipase activity levels, while the LPL mass was at the minimum level of the normal range. Abstract : We report a case of non‐alcoholic steatohepatitis complicated with acute pancreatitis induced by hypertriglyceridemia in a young Japanese woman. A precise examination of the lipid profile showed decreased lipoprotein lipase (LPL) and hepatic triglyceride lipase activity levels, while the LPL mass was at the minimum level of the normal range.